PG112 Exploring the influence of trainee attributes on simulation-based mental health training efficacy. (10th November 2020) - Saunders, Aleks; Vega, Marta Ortega; Ianelli, Hannah; Attoe, Chris; Cross, Sean
Abstract : Mental health is a growing sector of healthcare, in which patients who suffer untreated experience worse quality of life outcomes and lower life expectancy. In order to achieve the best possible care, training and subsequent evaluation is needed for those who work with patients experiencing mental health difficulties. Research suggests that age has the potential to impact training efficacy, in which older participants are significantly worse at retaining novel training skills compared to their younger counterparts. It has also been suggested that there are differences in preferred learning styles, and thus learning efficacy, between males and females. Thus, this paper sought to investigate these differences within the novel training method of high-fidelity, actor-based mental health simulation training, in order to identify factors that may affect training efficacy and subsequently patient outcomes. 829 participants attended simulation training courses and completed the Human Factors Skills for Healthcare Instrument pre- and post-course. Significant changes in HFSHI scores were found between pre- and post-course data across all participants, suggesting that simulation training can be universally effective as a method of pedagogy. Individuals within the ages of 25–29 reported significantly less mean change in HFSHI scores than those between 35–45. Career stage did not seem to mediate this effect. No differences in HFSHI scores were found across gender. The study concludes that simulation is an innovative training method that is effective across a variety of courses and professions. More research should be conducted to investigate why there may be differences in learning outcomes for different ages in regard to simulation, and to identify any other confounding factors that may influence these results. Reference: McManus, S., Bebbington, P., Jenkins, R., & Brugha, T. ( 2016). Mental health and wellbeing in England: Adult Psychiatric Morbidity Survey 2014. A survey carried out for NHS Digital by NatCen Social Research and the Department of Health Sciences, University of Leicester. Reedy, G. B., Lavelle, M., Simpson, T., & Anderson, J. E. ( 2017). Development of the Human Factors Skills for Healthcare Instrument: a valid and reliable tool for assessing interprofessional learning across healthcare practice settings. BMJ Simulation and Technology Enhanced Learning ;3(4):135–141.